A survey on predicting oil spills by studying its causes using deep learning techniques - Mona Mohamed Nasr; Fahd Kamal Al-Sheref; Yasmen Samhan Abd Elwahab (Institute of Advanced Engineering and Science, 2021)
It’s so easy to know the accidents as it’s already happened and solving these accidents is immediately handled, but searching for a solution for these accidents, don’t deny the existence of reasons that made accidents happen. Knowing the source of accidents will help in avoiding them to occur in the future. It’s an important field in searching as some human lives depend on the safety of such a field, so it’s so important to use a powerful technique to define these reasons as the research point in spill accidents and predicting accidents and to predict the occurrence of the accident before its happening depending on its reasons that lead to that accident in past times so with similar conditions it might happen an accident but it needs a sufficient data and a powerful technique such as deep learning techniques that give very precise results and by using this tool an Intelligent Model will build to predict oil spilling. In this survey paper, related work will be discussed to enhance that work.